PENGEMBANGAN MEDIA ADOBE FLASH BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA - Kiki Pratama Rajagukguk (LPPM STKIP AL MAKSUM, 2019)
The background of this depevelopment is lack of media usage in learning sciences that limited using books and blackboard. This development which aims to identify the feasibility and effectiveness of adobe flash learning media based on discovery learning developed. The development of learning media used ADDIE’s model of development. The development procedure which used in the research consists of five steps, namely: (1) analyze, (2) design, (3) development, (4) implementation, (5) evaluation. The data collecting instruments were assessment sheets for the material expert, media expert, instructional design expert, class teacher, and achievement test. The data analysis technique was the qualitative descriptive technique using score distributions and assessment scale categories. The result of research producing products that meet the eligibility criteria reached 3,80 that have a valid criteria and fit for use, also effectively used to improve students learning outcomes include mastery learning individual reached 85,7%, completness of classical study reached 80,5% and with N-gain percentage reached 0,68 with medium category.